Development and Characterization of an In Vitro Round Window Membrane Model for Drug Permeability Evaluations - Ruby Singh; Bhaskar Birru; Joachim G. S. Veit; Elizabeth M. Arrigali; Monica A. Serban (MDPI AG, 2022)
Hearing loss and balance disorders are highly common disorders, and the development of effective oto-therapeutics remains an area of intense research. Drug development and screening in the hearing research field heavily rely on the use of preclinical models with often ambiguous translational relevance. This often leads to failed advancement in the market of effective therapeutics. In this context, especially for inner ear-specific pathologies, the availability of an in vitro, physiologically relevant, round window membrane (RWM) model could enable rapid, high-throughput screening of potential topical drugs for inner ear and cochlear dysfunctions and could help accelerate the advancement to clinic and market of more viable drug candidates. In this study, we report the development and evaluation of an in vitro model that mimics the native RWM tissue morphology and microenvironment as shown via immunostaining and histological analyses. The developed three-dimensional (3D) in vitro model was additionally assessed for barrier integrity by transepithelial electrical resistance, and the permeability of lipophilic and hydrophilic drugs was determined. Our collective findings suggest that this in vitro model could serve as a tool for rapid development and screening of topically deliverable oto-therapeutics.